Assessment of thermobaric state and change of the mass balance in the subgkacial Lake Vostok after drilling-in - A. N. Markov; P. G. Talalay (Лëд и снег, 2015)
Estimation of temperature and pressure conditions in the subglacial reservoirs is one of the most important tasks of modern subglacial research, since it provides an adequate tool for predicting the process of their accessing. This paper presents the estimation of pressure in the subglacial reservoirs for different baric system statuses. Opening of isolated subglacial reservoirs is attended by disturbance of their thermobaric equilibrium, thus the conditions of phase transition are changed on the entire surface of the ice-water contact. At the same time reducing the pressure in the subglacial reservoirs leads to «lowering» of the phase transition of ice-water boundary and to the growth of additional layer of congelation ice on the entire bottom surface of the ice sheet contact with water. Realized accessing of Lake Vostok and technology re-entry involves water rise into the borehole from the lake as one of the steps to prevent pollution of relict water system. With the use of this technology the reliability of estimate the pressure in Lake Vostok is extremely important and, consequently, the value of the differential pressure when the borehole accesses with lake. The paper presents analysis of the possible consequences of incorrect estimation of the pressure in isolated water system of Lake Vostok, when the borehole accesses in conditions of incomplete compensation of subglacial water pressure by hydrostatic pressure of the drilling fluid column.